Circulating Myeloid‐Related Protein–8/14 is Related to Thromboxane‐Dependent Platelet Activation in Patients With Acute Coronary Syndrome, With and Without Ongoing Low‐Dose Aspirin Treatment. Issue 4 (18th July 2014) - Santilli, Francesca; Paloscia, Leonardo; Liani, Rossella; Di Nicola, Marta; Di Marco, Massimo; Lattanzio, Stefano; La Barba, Sara; Pascale, Silvia; Mascellanti, Marco; Davì, Giovanni
Abstract : Background: Platelet activation is involved in acute coronary syndromes (ACS). Incomplete suppression by low‐dose aspirin treatment of thromboxane (TX) metabolite excretion (urinary 11‐dehydro‐TXB2 ) is predictive of vascular events in high‐risk patients. Myeloid‐related protein (MRP)‐8/14 is a heterodimer secreted on activation of platelets, monocytes, and neutrophils, regulating inflammation and predicting cardiovascular events. Among platelet transcripts, MRP‐14 has emerged as a powerful predictor of ACS. Methods and Results: We enrolled 68 stable ischemic heart disease (IHD) and 63 ACS patients, undergoing coronary angiography, to evaluate whether MRP‐8/14 release in the circulation is related to TX‐dependent platelet activation in ACS and IHD patients and to residual TX biosynthesis in low‐dose aspirin–treated ACS patients. In ACS patients, plasma MRP‐8/14 and urinary 11‐dehydro‐TXB2 levels were linearly correlated ( r =0.651, P <0.001) but significantly higher than those in IHD patients ( P =0.012, P =0.044) only among subjects not receiving aspirin. In aspirin‐treated ACS patients, MRP‐8/14 and 11‐dehydro‐TXB2 were lower versus those not receiving aspirin ( P <0.001) and still significantly correlated ( r =0.528, P <0.001). Higher 11‐dehydro‐TXB2 significantly predicted higher MRP‐8/14 in both all ACS patients and ACS receiving aspirin ( P <0.001, adj R 2 =0.463 and adj R 2 =0.497) after multivariable adjustment. Conversely, plasma MRP‐8/14 ( P <0.001) and higher urinary 8‐iso‐prostaglandin F2α ( P =0.050) levels were significant predictors of residual, on‐aspirin, TX biosynthesis in ACS (adjusted R 2 =0.384). Conclusions: Circulating MRP‐8/14 is associated with TX‐dependent platelet activation in ACS, even during low‐dose aspirin treatment, suggesting a contribution of residual TX to MRP‐8/14 shedding, which may further amplify platelet activation. Circulating MRP‐8/14 may be a target to test different antiplatelet strategies in ACS.